Respostas

2014-03-22T04:23:29-03:00
X² - 4x = 45 
-X²- (-4x)-45=0
(-1).
X² - 4x +45 = 0
a= 1  b= 4  c= +45
▲= b
² - 4.a.c=
      (4)² - 4(1).(+45)=
      +16 – (+180)=  196
AGORA
 X = -b +/- V196
            2.a
 X= -( -4) +/- 14  =         X’ =  4 + 14 =  18  =  9                                                                       2                                       2                                                                                                               X" = 4 - 14 = 10  = 5                                                                                                               2                                                                             Agora substitua a fórmula do começo e verifique: x² - 4x =45                                                                                                                 9² - 4.9 = 45                                                                                                               81 - 36 = 45                                           ENTÃO A IDADE DELE É 9 ANOS.
1 1 1